Pengaruh Keterlibatan Kerja, Kepuasan Kerja, dan Organizational Citizenship Behavior pada Kinerja Pegawai Kantor Balai Pelestarian Kebudayaan Yogyakarta - Muhammad Kafal Faa'id; Ignatius Soni Kurniawan; Eko Yulianto (Politeknik Bisnis Indonesia, 2023)
Low performance is caused by employees' understanding of the targets that must be pursued not being fully understood, and the organization has not identified factors that affect employee performance. This study examines the effect of job involvement, job satisfaction, and organizational citizenship behavior (OCB) on Kantor Balai Pelestarian Kebudayaan (BPK) Yogyakarta. This research is quantitative, and primary data was taken using a questionnaire taken by accidental sampling of 46 respondents. Sampling is done using the Slovin formula. Data were collected through direct surveys and then processed using multiple linear regression analysis. The results showed that job satisfaction has a significant positive effect on employee performance. Job involvement and OCB have no significant effect on employee performance. The implication is to maintain employee satisfaction and the performance of workers in the agency.